2010
DOI: 10.1111/j.1365-2672.2010.04816.x
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of commercial DNA extraction kits for the isolation of bacterial spore DNA from soil

Abstract: The results of this study aid in the selection of an appropriate DNA extraction kit for a given soil sample. Its application could expedite sample processing for real-time PCR detection of a pathogen in soil.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
91
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 113 publications
(94 citation statements)
references
References 56 publications
(108 reference statements)
2
91
0
Order By: Relevance
“…The results showed that both the quantity (yield of extraction) and the quality (purity, degree of degradation, easiness of amplification) of the extracted DNA depended on the extraction method and the type of environmental sample (Table 3), which was in agreement with earlier observations reported in the literature [9,10,14,32,33]. Moreover, Table 6.…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…The results showed that both the quantity (yield of extraction) and the quality (purity, degree of degradation, easiness of amplification) of the extracted DNA depended on the extraction method and the type of environmental sample (Table 3), which was in agreement with earlier observations reported in the literature [9,10,14,32,33]. Moreover, Table 6.…”
Section: Discussionsupporting
confidence: 82%
“…However, the E.Z.N.A. conventional method provided much lower yields of extraction in comparison to its alternative method, as was also observed in other investigations [32,33]. Because of the demonstrated conflicts among different extraction methods and criteria, the selection of the optimum method for different types of soil was not straightforward (Table 4).…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations